Trans Parenthood and the Meaning of 'Mother', 'Father' and 'Parent'—R (McConnell and YY) v Registrar General for England and Wales [2020] EWCA Civ 559. (15th March 2021) - Brown, Alan
Abstract: In R (McConnell and YY) v Registrar General for England and Wales [2020] EWCA Civ 559, the Court of Appeal held the Registrar General was correct to register a trans man, who had given birth after the issuing of his gender recognition certificate, as 'mother' on his son's birth certificate. In their judgement, the court rejected the appellants' contention that the Gender Recognition Act 2004 should be construed to allow registration as either 'father' or 'parent'. The court further held that the interference with the appellants' Article 8 rights which resulted from the registration as 'mother' was proportionate and justified.